Impact of Market Segmentation Practices on the Profitability of Small and Medium Scale Enterprises: Case Research (Global Business Management Review (GBMR), 2022)
This study is designed to assess the impact of market segmentation practices on the profitability of small and medium scale furniture manufacturing enterprises in Hawassa city. Market segmentation has been defined as dividing a market into smaller groups of buyers with distinct need, characteristics or behavior, which might require separate products or marketing mixes. Small and medium scale business is a business which is independently owned and operated, not dominant in its field of operation and meets certain standard of number of employee and capital. Profitability for a period in this study is typically defined as the earnings of an investment during the period divided by the capital employed in the investment at that time. In order to achieve the objective of the study, both primary and secondary data sources were employed. The data were collected through a questionnaire which has three parts, i.e. demographic, market segmentation and profitability questionnaires which are developed based on the theoretical assessment of related literatures. The questionnaires were distributed to 60 SMEs in which only 48 were fully completed and returned. The data collected were analyzed using SPSS software such as correlation and multiple Regression analysis. On the basis of the data obtained from the respondents, the study identified that there exists a positive significant relationship between market segmentation practices and profitability ranging from medium to substantial in the selected sample SMEs. The findings of this study also revealed the levels and bases of market segmentation used in the enterprises as well as their relationship with profitability as its major findings. Almost all the enterprises gained moderate and substantial profits by implementing market segmentation practices in their enterprises. However, they were also found with a problem of selecting appropriate levels and bases of segmentation. Moreover, they were facing difficulties in evaluating the effectiveness of their segmentation practices which prohibited them from generating high profits from their segments. Based on the findings of the study, the researcher has forwarded some recommendations to the owners and managers of small and medium scale furniture manufacturing enterprises which are found in Hawassa city.